Teachers’ Perception of the Concept and Objectives of Citizenship Education in Edo South Senatorial District - Egharevba, John; Abiola, Olatunde (NIU Journal of Social Sciences; Vol 5 No 4 (2019): KIU Journal of Social Sciences, Vol. 5 No. 4, December 2019, 2020)
This study investigated teachers’ perception of the concept and objectives of citizenship education by Social Studies teachers in Edo State. A sample of 100 Social Studies teachers were randomly selected from all the public secondary schools in Edo South Senatorial District using the table of random numbers. Data were collected through questionnaire designed by the researchers and analyzed with the z-test of independent samples. These were considered suitable because the sample used was further divided into independent sample. Results revealed that there is no difference between the ways the experienced Social Studies teachers and the less experienced perceived the objectives of Citizenship Education. Based on the result, it was recommended, among others, that there should be full scale implementation of the citizenship education curriculum in schools because of the growing incivility in the country. Keywords: Perception, Concept, Objectives, Citizenship education and Social studies.